2021
DOI: 10.1088/1755-1315/845/1/012077
|View full text |Cite
|
Sign up to set email alerts
|

Gluten-free products from chickpea flour

Abstract: The paper discusses the possibility of the expansion of the range of flour culinary products for a gluten-free diet using chickpea flour. The analysis of the chemical composition of wheat and chickpea flour, as well as the glycemic index of all components of the recipe of the developed flour culinary product is presented. The possibility of partial and complete replacement of wheat flour with chickpea flour with the addition of caraway, lemon peel and potato starch is studied. It is found that the inclusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Furthermore, these bakery products can be consumed by vegans and vegetarians because they are enriched in proteins and antioxidants but produced without animal-derived ingredients. 55,56 In conclusion, we demonstrated that chickpea flour derived from WD-treated plants has a higher content of polyphenols with respect to those of CF and BF. The obtained peptides maintained a similar trend with those of flour in terms of polyphenol content and antioxidant activity.…”
Section: ■ Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, these bakery products can be consumed by vegans and vegetarians because they are enriched in proteins and antioxidants but produced without animal-derived ingredients. 55,56 In conclusion, we demonstrated that chickpea flour derived from WD-treated plants has a higher content of polyphenols with respect to those of CF and BF. The obtained peptides maintained a similar trend with those of flour in terms of polyphenol content and antioxidant activity.…”
Section: ■ Discussionmentioning
confidence: 57%
“…Thus, these biscuits could be used for treating different pathologies or in gluten-free diets. Furthermore, these bakery products can be consumed by vegans and vegetarians because they are enriched in proteins and antioxidants but produced without animal-derived ingredients. , …”
Section: Discussionmentioning
confidence: 99%
“…Okrem toho tieto suroviny neobsahujú lepok a lepku podobné bielkoviny, preto môžu byť použité aj pri výrobe bezlepkových produktov (Melini a Melini, 2021;Necheporuk et al, 2021;Maghaydah et al, 2022). ZÁVER Strukoviny a pseudocereálie predstavujú nutrične významné suroviny s mnohými zdravotnými benefitmi (Kumari, Sangeetha, 2017).…”
Section: Výsledky a Diskusiaunclassified